The frontier in American culture : an exhibition at the Newberry Library, August 26, 1994 - January 7, 1995 - White, Richard, 1947- (The Library, 1994)
Log cabins and wagon trains, cowboys and Indians, Buffalo Bill and General Custer. These and other frontier images pervade our lives, from fiction to films to advertising, where they attach themselves to products from pancake syrup to cologne, blue jeans to banks. Richard White and Patricia Limerick join their inimitable talents to explore our national preoccupation with this uniquely American image. Richard White examines the two most enduring stories of the frontier, both told in Chicago in 1893, the year of the Columbian Exposition. One was Frederick Jackson Turner's remarkably influential l.